CHANGES IN RAINFALL ON PLANTING AREA AND OIL PALM PRODUCTION IN THE HIGHLANDS OF DELI SERDANG DISTRICT, NORTH SUMATRA - Sumarno; Yenni Asbur; Murni Sari Rahayu (RADJA PUBLIKA, 2025)
The research was conducted from February to April 2024 in Deli Serdang Regency, North Sumatra Province. Rainfall is a very important climatic factor in influencing crop growth and production, including oil palm. The purpose of this study was to examine how rainfall affects the planting area and production of oil palm in the highlands of North Sumatra. The study used secondary data in the form of information on planting area and production in Deli Serdang Regency during 2019-2023, obtained from the Deli Serdang Regency Agriculture Office and the Food Security and Horticulture Office, as well as the Meteorology, Climatology and Geophysics Agency in Deli Serdang, North Sumatra. The results showed that there was a negative correlation between rainfall and oil palm planting area and production, with values of -0.599 and -0.645, respectively. This means that there is a moderate negative relationship between rainfall and oil palm planting area and production, where higher rainfall results in lower oil palm planting area and production, although this is not statistically significant.